The Development of Stock Endowments as One of The Philanthropies For Muslim Investors - Ulfa, Nadia; Wirdyaningsih, Wirdyaningsih (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract. The inauguration of the stock waqf by the Indonesia Stock Exchange in 2019 and a significant number of Sharia investors have led to considerable potential in stock endowments. This study examines the development of stock endowments for Muslim investors, using a normative-empirical legal study with data obtained from a survey involving stock investors and a literature study. The study concludes that the public had practiced stock waqf or money waqf even before the issuance of the MUI fatwa in 2002 concerning Money Endowments, while stock endowments were officially launched by IDX in 2019. Based on the questionnaire distributed to investors, most knew the stock endowments. Law No. 41 of 2004 on Waqf has been knowledgeable, but the waqf distribution was improperly distributed.Abstrak. Diresmikannya wakaf saham oleh Bursa Efek Indonesia pada tahun 2019 dan jumlah investor syariah yang signifkan menjadi potensi wakaf saham yang cukup besar. Penelitian inimengkaji perkembangan wakaf saham bagi investor Muslim, dengan menggunakan kajian hukum normatif-empiris. Data diperoleh melalui survei kepada investor saham dan studi literatur. Peneliti menyimpulkan bahwa masyarakat telah melakukan wakaf saham atau wakaf uang sejak sebelum keluarnya fatwa MUI tahun 2002 tentang Wakaf Uang. Sedangkan wakaf saham resmi diluncurkan oleh BEI pada tahun 2019. Berdasarkan kuisioner yang dibagikan kepada investor, mereka familiar dengan wakaf saham. Namun, meskipun Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf sudah banyak diketahui, namun penyaluran wakaf tidak tersalurkan dengan baik.